2002
DOI: 10.1055/s-2002-33220
|View full text |Cite
|
Sign up to set email alerts
|

A Defoaming Agent Should Be Used with Pronase Premedication to Improve Visibility in Upper Gastrointestinal Endoscopy

Abstract: Premedication as in group E provided the clearest endoscopic visibility. Without the application of DMPS, pronase alone cannot improve endoscopic visibility. Pronase does not influence H. pylori identification using the CLO test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 5 publications
(8 reference statements)
1
38
0
3
Order By: Relevance
“…Hence the findings of this study are in keeping with those of several previous studies demonstrating improvements in gastric mucosal visibility with a pre-gastroscopy drink containing a mucolytic and a defoaming agent 9 10 14. This is the first study to specifically assess the effect of the combination of simethicone and NAC on the quality of mucosal visibility in a Western population.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Hence the findings of this study are in keeping with those of several previous studies demonstrating improvements in gastric mucosal visibility with a pre-gastroscopy drink containing a mucolytic and a defoaming agent 9 10 14. This is the first study to specifically assess the effect of the combination of simethicone and NAC on the quality of mucosal visibility in a Western population.…”
Section: Resultssupporting
confidence: 88%
“…Several studies have demonstrated that drinking a defoaming agent before a procedure improves mucosal visibility 7 8. Results are conflicting among studies that have examined whether the addition of a mucolytic such as N-acetylcysteine (NAC) to a defoaming agent offers any further benefit 9 10 11 12 13.…”
Section: Introductionmentioning
confidence: 99%
“…5,13 Some investigators have reported that premedication with a defoaming agent and pronase improved visibility to a greater degree than did pronase alone during upper GI endoscopy. 14 In addition, others have reported that premedication with a defoaming agent and acetylcysteine, a mucolytic agent, or pronase improved visibility during EUS. 6,15 No special preparation is usually required for EUS of the upper GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 20 mg scopolamine butylbromide was given by intramuscular injection, and 50 ml of saline solution containing 1 g bicarbonate sodium and 20 000 units α-chymotrypsin was taken orally 15–20 min before endoscopy 9 12…”
Section: Methodsmentioning
confidence: 99%